Exploring the microscopic mechanism of pseudocapacitance with electronic structures in monolayer 1T-MoS2 electrodes for supercapacitors. (3rd April 2019) - Zhang, Zhenzhou; Wu, Maokun; Wang, Lijing; Wang, Jin; Cheng, Yahui; Li, Luyan; Dong, Hong; Liu, Hui; Hong, Zhanglian; Cho, Kyeongjae; Lu, Feng; Wang, Weichao; et al.
Abstract : The microscopic mechanism of pseudocapacitance with electronic structures in monolayer 1T-MoS2 and the pseudocapacitance manipulation by defects have been elucidated. Abstract : Quasi-two-dimensional 1T-MoS2 is a promising pseudocapacitance ( C redox ) electrode material due to its large specific surface area, superior electrical conductivity and mechanical stability. However, the microscopic mechanism of C redox and its further manipulation via modulating the structures and electronic structures are still unclear. Thus, the C redox of monolayer 1T-MoS2 has been explored based on first-principles calculations. For monolayer 1T-MoS2 adsorbed by H + ions on one side or both sides, a band gap opens, decreases and even disappears with the coverage increase in H + ions up to 100%. In this process, the charge transfer from the monolayer 1T-MoS2 to the adsorbed H + ions almost linearly increases with the coverage increase in the H + ions. In contrast, the potential change rate of the monolayer 1T-MoS2 reduces, resulting in the enhancement of C redox . Herein, the maximum values of C redox reached ∼76.7 μF cm −2 (252.8 F g −1 ) and ∼213.7 μF cm −2 (704.5 F g −1 ) for the 100% coverage of H + ions on one side and both sides, respectively. Furthermore, the manipulation of C redox in the monolayer 1T-MoS2 could be realized through intrinsic defects engineering. Particularly, the C redox was greatly improved in the system with S vacancies. These results would provide significantly fundamental insights for understanding the correlation between the C redox and the electronic structures of 1T-MoS2 and other similar quasi-two dimensional materials.